The complete chloroplast genome sequence of Bolboschoenus planiculmis (Cyperaceae). Issue 1 (2nd January 2022) - Ning, Yu; Dong, Shu Bin; Zhao, Yu Xin; Pan, Zhe; Ma, Hua
Abstract: Bolboschoenus planiculmis is a typical wetland sedge with both ecological and agricultural value. We report the first complete chloroplast genome sequence of this species. The total genome size is 186, 539 bp, containing a large single-copy region (LSC) of 104, 654 bp, a small single copy region (SSC) of 9, 659 bp and two inverted repeats (IRs) of 36, 113 bp by each. The GC content is 33.59%. The genome encodes 105 unique genes, including 71 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. Phylogenetic analysis shows this species has a strong sister relationship with Cyperus . Our work could be helpful in understanding the evolution of Cyperaceae.